The design, construction, and testing of an instrument to measure Latina's health beliefs about breast cancer and screening - González, Patricia, author; Borrayo, Evelinn, advisor (Colorado State University. Libraries, 2007)
Hispanic women's (Latinas) survival from breast cancer (BC) is lagging behind the survival rates of non-Hispanic white women, possibly due to more advanced stage of disease at diagnosis (Fernandez-Esquer, Espinoza, Torres, Ramirez, & McAlister (2003). Fewer baseline and routine BC screening procedures among Latinas may explain the observed delay in diagnosis. Participation in BC screening is influenced by various socio-demographic, socio-cultural and psychological factors. The purpose of this study was to develop and test the Latina Breast Cancer Screening (LBCS) Scale, which measures cultural health beliefs that might influence Latinas' decision to engage in regular BC screening. More specifically, this study tested the LBCS scale to establish its psychometric properties: the instruments validity and reliability. Content validity was assessed by having a research team review the items for relevancy, accuracy and wording of the items. First, a 60-item and an 80-item version of the LBCS was developed and administered to 288 Latinas. Next, principal components analyses and reliabilities aided in reducing the scale to 36 items. This study was successful at identifying six distinct factors, therefore contributing to the scale's construct validity. Lastly, the LBCS scale was tested with 155 participants to establish its psychometric properties: the instrument's validity and reliability. The LBCS displayed strong internal consistency. As expected, the LBCS scale was significantly and positively correlated with the Group-Based Medical Mistrust Scale items (i.e., medical mistrust), the fatalism inventory, and the Cultural Health Attributions Questionnaire thus establishing convergent validity. In addition, as predicted traditional scores on the LBCS were significantly and negatively correlated to BC knowledge, thus establishing discriminant validity. This study suggests that the LBCS is a reliable and valid scale to assess cultural BC health beliefs. This study provides a contribution to the literature on Latinas BC beliefs through the development of an instrument that measures cultural health beliefs and norms that past research studies have alluded to but have not been able to measure. In conclusion, BC prevention efforts should focus on increasing awareness among Latinas and medical healthcare providers about cultural health beliefs (i.e., Feeling Healthy, Feeling Indecent, Feeling Threatened) which play an important role in BC screening behaviors.
Keywords: breast cancer; cancer screening; cultural beliefs; health beliefs; Latina; social psychology; women's studies; Hispanic American studies